Pemanfaatan Hewan Sebagai Obat Tradisional oleh Etnik Lom di Bangka - Budi Afriyansyah; Nur Annis Hidayati; Hapis Aprizan (Faculty of Mathtmatics and Natural Sciences, 2016)
Knowledge about the use of animals as a traditional medicine is benefit to society and must be saved. This knowledge can be used as a source of reference for researchers in the development of science and alternative ideas in the present. The purpose of this study were reveal diversity of animal drug ethnic Lom in Bangka and Lom ethnic knowledge traditional in Bangka about diversity of animal drug and used of animals as a traditional medicine. Research was conducted from January to May 2015 in Air Abik, Pejem, and Mapur village. Methods used in this research were purposive sampling (determine informans), interview and direct obeservation. Result showed that ethnic Lom used 24 species animals as medicine from 10 class in traditional medicine. The animal species most used is from the class of mammals (38%). Seen from habitat, animals are used as traditional medicines are mostly terrestrial animals (44%) are living wild in the woods. The most used animal that is part of the body (76%). Results of grouping by type of disease and the type of animals that have properties as a medicinal ingredient, there were 18 types of diseases that can be cured (medical or non-medical disease). Ethnic Lom had a good knowledge about the diversity of animal species and benefit of drugs, but this knowledge is declining and began to be forgotten by the people of ethnic Lom. The results of the interviews and observations in the field showed animal species of cacing tanah (Pheretima sp.) and undur-undur (Myrmeleon sp.) has the potential to be developed, not only as a animals drug used ethnic Lom communities but also can improve the economy of communities in the region.